The Evolution of Sustainable Business Practices: A Bibliometric Study on Corporate Social Responsibility and Green Marketing - Loso Judijanto; Adi Suroso; Achmad Choerudin (Sciences du Nord Economics and Business, 2024)
This bibliometric study explores the evolution and integration of Corporate Social Responsibility (CSR) and Green Marketing within sustainable business practices over the past two decades. Utilizing data from major databases such as Web of Science and Scopus, the research employs keyword co-occurrence and citation analysis to map the thematic landscape and identify research hotspots and trends. Findings highlight "corporate social responsibility" and "green marketing" as focal points, with increasing scholarly attention directed towards linking these areas to competitive business advantages and brand enhancement strategies. The study reveals a transition in focus from traditional environmental concerns to strategic business functionalities, integrating sustainability with profitability. Additionally, areas such as digital green marketing and supply chain sustainability are identified as emerging fields of interest, suggesting potential for future research. The results contribute to a deeper understanding of the trajectory and impact of CSR and Green Marketing in contemporary business practices, offering insights for academics, practitioners, and policymakers aiming to foster more sustainable enterprises.